Responsible Debt Collection in Emerging Markets - International Finance Corporation (Washington, DC, 2015)
Emerging market economies have been experiencing high credit growth and high delinquency rates amongst retail banking customers in recent years. However, collections practices have not always kept pace with this rapid growth; many collectors still rely on relatively unstructured processes and weak oversight frameworks. It is therefore important to consider how fair and ethical treatment of borrowers can be better promoted in these markets. To this end, International Finance Corporation (IFC) commissioned a study in 2009 to examine the question of what guiding principles should financial institutions follow to raise their responsible and ethical standards in collections. IFC has subsequently commissioned Oliver Wyman to study existing global retail debt collections practices and recommend tangible actions that lenders and collectors can take to promote responsible and ethical standards in the field. The conclusions of this study are based on field research conducted by IFC and Oliver Wyman, industry experts analysis and opinion, and a survey of institutions in 20 emerging markets.